L’évaluation de l’implantation et des retombées du service des aides à la vie étudiante en milieu universitaire - Audrey Dupuis; Julie Lane; Amélie Soulard; Johanne Desrosiers; Pascale Morin; Emmanuelle Jasmin; Bruno Collard; Jocelyne Faucher (Revue Internationale de Pédagogie de l’Enseignement Supérieur, 2023)
The precarious mental health of university students is worrying and can have many consequences on their lives. Support services are offered by universities, but they generally are local initiatives that remain under evaluated. The Université de Sherbrooke has established a new service to support students on a personal, academic and professional level: the Aides à la vie étudiante (AVE) initiative. This article aims to assess the implementation process and the impact of the AVE initiative, according to Chens’ model (2015). A mixed methodology is used to do so. Semi-structured individual interviews were conducted with five university partners, four AVE and nine students. Questionnaires were also used and completed by 47 AVE and 70 students. An appointment-tracking tool completed by AVE was also used. The results show how the AVE initiative was implemented, the factors that favor or hinder its implementation and its impact and are then discussed and linked to other studies. The factors that facilitate or hinder the implementation identified can help determine the guidelines to be considered in the implementation of a support service for students in an university setting. Also, the predominantly positive impact of the initiative on the AVE, students and university supports the relevance of this type of support service.